Design Teaching Stories - Moura, Mônica (DAT Journal, 2020)
This article presents part of the results of the research developed in the doctoral studies and expanded in the post-doctoral investigations regarding teaching in design and its history constituted through the relations established between groups, movements and actions that influenced or had repercussions in the formation of schools of free or formal education, either foreign and Brazilian. The objective is to establish a chronological path bringing together several manifestations that allow new reflections and analyzes, dispelling myths and models and allowing critical appraisals with the intention of collaborating with the area of teaching in design and with the development of new pedagogical political projects. The adopted method is of qualitative character constituted by literature review, documentary and field research. The theoretical framework is based on historians, educators, critics and design professionals, such as Meggs and Purvis (2009), Bürdek (2006), Archer (2004), Wollner (2002), Ferlauto (2002), Fiell (2000), Denis (2000), Heskett (1997), Souza (1997), Niemeyer (1997), Lima (1997), Droste (1994), Pevsner (1994), Wick (1989), Zanini (1993) and, also, in studies by the philosopher Agamben (2009).